Kewenangan Bawaslu Kabupaten/Kota dalam Menyelesaikan Sengketa Proses Pemilu Menurut Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilu - Adam Sani; Ilka Sandela; Nila Trisna (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
The purpose of this study is to determine the authority of the Regency/City General Election Supervisory Body (Bawaslu) in resolving electoral process disputes based on Law Number 7 of 2017 concerning Elections. The research method used is normative juridical through a statutory approach. The main data sources in this study consist of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out qualitatively through analytical and prescriptive methods. The conclusions drawn by the researcher from the results of this study were carried out using a qualitative descriptive normative method. The results of the research are that the Regency/Municipal General Election Supervisory Body (Bawaslu) has the authority to resolve electoral process disputes that occur in regencies/municipalities, both among election participants or election participants with the KPU due to the issuance of a Decree or Official Report. The process of implementing electoral process disputes is carried out through mediation and adjudication. Election process dispute decisions made by Bawaslu are final and binding, except for election process disputes relating to the verification of Election Political Parties, determination of DCT members of DPR, DPD, Provincial DPRD, and Regency/Municipal DPRD as well as the determination of Candidate Pairs that can be sued to the Election Commission. Administrative Court (PTUN). It is recommended to Bawaslu to strengthen the human resources of Bawaslu members at the Regency/City level, especially the ability of Bawaslu members to resolve disputes in the election process.Keywords: Authority, Regency/City, Dispute, Election